Fingerprint abnormalities in systemic sclerosis: Results of a single center pilot study - Kodishala Chanakya; Liza Rajasekhar (Indian Journal of Rheumatology)
Background: Fingertip abnormalities in the form of digital ulcers and gangrene is well known in systemic sclerosis (SSc), but little has been described about the frequency and systemic associations of finger print (FP) abnormalities in these patients. Our objective was to study the FP abnormalities in SSc patients and find possible association with digital vasculopathy. Methods: Patients with SSc and SSc overlap with other connective tissue diseases were screened for FP abnormalities using a Standardization Testing and Quality Certification Directorate-certified biometric FP scanner. FP quality assessment was done by recording the National Institute of Standards and Technology FP Image Quality (NFIQ) scores. NFIQ's 5 levels of quality are intended to be predictive of fingerprint matching. NFIQ = 1 indicates high quality and NFIQ = 5 indicates poor quality FPs. Social difficulties due to fingerprint abnormalities were noted. Ten healthy controls were included for comparison. Results: Of 37 patients, 29 with SSc and 8 with overlap syndromes, 15 (40.5%) had FP abnormalities in the form of nonrecognition of at least one finger with a median of 2 fingers (range 1–6). The mean NFIQ score of these patients was 4.5 (poor) while mean NFIQ scores in SSc was 3.8. All FPs of 10 controls were recognized, and the mean NFIQ score was 2.2 indicating a better FPs quality. There was no association of FP abnormalities with digital vasculopathy. Conclusions: In this pilot study, we found that fingerprint abnormalities occur frequently in SSc patients. Documentation of this abnormality should allow the use of other biometric tools for personal identification.